The decision making analysis of increasing storage capacity of sutami reservoir with Analytical Hierarchy Process (AHP) approach - BAMBANG GUTOMO; UDISUBAKTI CIPTOMULYONO; EKOBUDI SANTOSO (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aims to use the Analytical Hierarchy Process (AHP) technique, a form of multi-criteria decision-making, to rank the relative merits of potential courses of action. Through pairwise comparisons based on importance levels, AHP unites different individuals’ qualitative, subjective evaluations into a collective evaluation of decision-making.Method: In this study, we will draw from existing literature on water resource management and planning to establish our criteria and sub-criteria. Experts in a dam, reservoir, and water resource management use FGD to finalize criteria/sub-criteria because of a knowledge gap between the two sets of studies. After collecting data from the FGDs, the criteria and sub-criteria are used in an AHP to rank a set of potential solutions.Findings: The following is the outcome of applying weights to the pairwise comparisons we conducted using the criteria of social, environmental, technical, and economic aspects: With 36.2% of the vote, the option of raising the dam body by 5 meters is deemed most important. In terms of alternatives, a 0.5-meter-higher spillway comes in second with a weight of 25.7%, while dredging sediments to the same depth as sediment inflow comes in third with a weight of 20.5%, and maintaining the current configuration receives the least amount of weight at 17.7%.Implications/Novel Contribution: All stakeholders must back and contribute to the development of research aimed at extending the useful life of existing reservoirs. It is common knowledge that all reservoirs have a finite amount of time before they must be shut down. Old, inefficient reservoirs are expensive to keep up and close. However, a new dam will not come cheap, and finding a suitable site is uncertain.